El llamamiento en garantía en el proceso arbitral en Colombia : ¿arbitraje obligatorio o voluntario?. (2017)
For several years the concept of a third party has been conceived, as far as the procedural doctrine in Colombia is concerned, from a confused perspective, specifically in the case of the so-called guarantee, leaving aside the fact that although at the beginning of the process could not appear clearly as one of the parties that will intervene in a main way, it will be a supervening party, which should be interpreted in coherence with what one might say is forced arbitration in Colombia; to the extent that the study of constitutionality of the aforementioned rule presents some contradictions that will be reviewed in the development of this article.